The Angular Relationships Between the Coracohumeral Ligament and Adjacent Shoulder Structures Are Variable - Robert L. Parisien, M.D; Kevin J. McHale, M.D; Dinesh Dhanaraj, M.D; Antonio Cusano, M.D; John D. Kelly, IV, M.D (Elsevier, 2021)
Purpose: To describe the arthroscopic anatomy of the coracohumeral ligament (CHL) in relation to visible anatomic reference points to aid in the execution of a more effective arthroscopic medial-lateral rotator interval closure. Methods: Detailed dissection to identify the CHL was performed in 4 shoulders from 2 fresh-frozen donor cadavers with a deltopectoral approach. The angular relationship between the CHL and the superior border of the subscapularis tendon was determined via gross dissection. Arthroscopic images were used to determine the angular position of the CHL in relation to both the glenoid articular surface and the intraarticular segment of the tendon of the long head of the biceps brachii (LHB). Results: Analysis of 4 cadaveric shoulders via gross dissection demonstrated the CHL to subtend a mean angle of 29° (range 16° to 39°) with respect to the superior border of the subscapularis tendon. Arthroscopic analysis of 4 cadaveric shoulders demonstrated the CHL to subtend a mean angle of 59° (range 38° to 77°) with respect to the glenoid articular surface. Additionally, arthroscopic analysis of 2 cadaveric shoulders demonstrated the CHL to subtend a mean angle of 29° (range 11° to 47°) with respect to the LHB tendon. Conclusion: Although the position of the CHL in relation to the subscapularis tendon, glenoid articular surface, and LHB tendon demonstrates a moderate degree of anatomic variability, these structures provide valuable anatomic reference points for the identification of the course of this significant static shoulder stabilizer. Clinical Relevance: Comprehensive understanding of the angular relationships between the CHL and adjacent shoulder structures may assist with the execution of a more effective arthroscopic rotator interval closure.